Cancer risk in Vietnam war veterans from the Korean Vietnam war veterans’ health study cohort - Lee, Wanhyung; Park, Soyoung; Kang, Seong-Kyu; Ham, Seunghon; Yoon, Jin-Ha; Choi, Won-Jun (Frontiers in Oncology, 2023)
During the Vietnam War, several unknown chemicals, such as Agent Orange, were used in Vietnam by the military. Therefore, there have been continuous health concerns among the Vietnamese population and veterans exposed to these hazardous chemicals. This study aimed to investigate the risk of all cancers and also organ-specific cancers among Korean veterans of the Vietnam War. This study used a national representative cohort that included all Korean Vietnam War veterans as the interest group, with 1:4 age-sex-region-matched general Korean citizens as the reference group, from 2002 to 2018. Age-standardized incidence ratios (SIRs) and 95% confidence intervals (CIs) were calculated for all cancers and for 31 organ-specific cancer categories based on the medical facility visit data. An increased SIR of 1.07 (95% CI, 1.06–1.08) was observed for all cancers among the veterans. There was a significantly increased risk of cancer among 22/31 organ-specific cancers, with 18 cancer categories showing a significantly higher risk than all cancers. The highest risk was observed for “malignant neoplasms of other parts of the central nervous system” (SIR, 1.71; 95% CI, 1.51–1.92). This study evaluated the risk of cancer among Korean veterans of the Vietnam War.